Discipline The Body Through The Fitness Centre During and After The Covid-19 Pandemic - Teguh Putranto; Bagong Suyanto; Septi Ariadi (IKOMIK: Jurnal Ilmu Komunikasi dan Informasi, 2021)
One of the sectors affected by the Covid-19 pandemic is the economic sector. Fitness centres are one of the industries affected by this pandemic due to government policies in imposing social restrictions on social distancing to reduce the spread of the corona virus. The purpose of this study was to determine how the communication strategy of fitness centres as part of the capitalist industry such as Urban Athletes, in disciplining the body during and after the Covid-19 pandemic. The method used in this research is Krippendorff content analysis on Instagram @urban.athletes posts during the period January 2021 to February 2021. The conclusion obtained is that Urban Athletes revives the lifestyle of sports during and after the Covid-19 pandemic by providing fantasies to maintain body condition during a pandemic. Urban athletes use the bodies in a disciplined manner to follow a lifestyle of sports to keep their bodies fit during a pandemic.